The house across the lake eaudiobook A novel. - Sager, Riley (Penguin Audio, 2022)
THE INSTANT NEW YORK TIMES BESTSELLER Named a most-anticipated summer book by USA Today , People , E! News, Cosmopolitan , PureWow , CNN.com, New York Post , CrimeReads, POPSUGAR , and more  The bestselling author of Final Girls and Survive the Night is back with his “best plot twist yet.” ( People , "Best Summer Books") Be careful what you watch for . . . Casey Fletcher, a recently widowed actress trying to escape a streak of bad press, has retreated to the peace and quiet of her family’s lake house in Vermont. Armed with a pair of binoculars and several bottles of bourbon, she passes the time watching Tom and Katherine Royce, the glamorous couple living in the house across the lake. They make for good viewing—a tech innovator, Tom is powerful; and a former model, Katherine is gorgeous. One day on the lake, Casey saves Katherine from drowning, and the two strike up a budding friendship. But the more they get to know each other—and the longer Casey watches—it becomes clear that Katherine and Tom’s marriage isn’t as perfect as it appears. When Katherine suddenly vanishes, Casey immediately suspects Tom of foul play. What she doesn’t realize is that there’s more to the story than meets the eye—and that shocking secrets can lurk beneath the most placid of surfaces.   Packed with sharp characters, psychological suspense, and gasp-worthy plot twists, Riley Sager’s The House Across the Lake is the ultimate escapist read . . . no lake house required.